INSTITUTE OF NATIONAL PERSONAL AUTONOMY: THE EXPERIENCE OF IMPLEMENTATION IN THE WESTERN UKRAINIAN PEOPLE’S REPUBLIC - Гон, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the origins of the principle of national personal autonomy and its essence, defending the principle of autonomy as a mean of protecting of the interests of their “own” by those social groups whose members have common social and cultural values. The feature of introduction of national personal autonomy in Western Ukrainian People’s Republic is that the political elite of this country tried to put it into the social practice in conditions of the military-political conflict.